Bodies that matter, bodies that don't: selective disembodiment in the early Wired magazine (1993–1997). Issue 3 (2nd July 2020) - Ferrari, Elisabetta
Abstract: This article investigates the relationship between disembodiment and cyberspace in early internet culture by analysing how bodies are represented in Wired magazine. Using a multi-stage qualitative analysis of the cover images, the cover titles and the cover articles of the magazine between 1993 and 1997, it reconstructs Wired 's discourse on bodies and cyberspace. The article suggests that Wired employs a discourse that I term selective disembodiment, a white male fantasy in which white women and people of colour matter only when they are disembodied in cyberspace, and only as disembodied entities: the voice and recognition they acquire by inhabiting cyberspace does not carry over in their embodied lives. This operates a political differentiation: between bodies that matter and bodies that don't. It is a vision of politics and society that, while superficially inclusive, downplays and curtails the agency of non-white, non-male bodies and still has implications for the internet today.